Acyclovir-loaded chitosan nanoparticles for ocular delivery - N N, Rajendran; R, Natrajan; Kumar R, Siva; S, Selvaraj (Asian Journal of Pharmaceutics (AJP), 2014)
The topical application of acyclovir as eye ointment remains a concern for effective management of various ocular viral diseases owing to poor ocular drug bioavailability. Hence the present study was aimed to develop and evaluate nanosphere colloidal suspension containing acyclovir as potential ophthalmic drug delivery system. The acyclovir-loaded chitosan nanoparticles were prepared by ionic gelation of chitosan with tripolyphosphate anions. The nanoparticles were characterized by scanning electron microcopy, zeta potential analyser, differential scanning calorimetry (DSC) and Fourier transform infrared Spectroscopy. All the prepared formulations resulted in nano-range size particles (200-495 nm) and displayed spherical smooth morphology with zeta potential (+36.7 to +42.3 mV).The encapsulation efficiency and loading capacity were 56-80% and 10-25%, respectively. The acyclovir-loaded chitosan nanoparticles displayed more crystallinity than acyclovir. The in vitro diffusion profile of acyclovir from the nanoparticles showed a sustained release of the drug over a period of 24 hrs. Kinetic release profiles of acyclovir from nanoparticles appeared to fit best with Higuchi model with zero order and the non-Fickian diffusion was superior phenomenon. Thus the results suggest that acyclovir-loaded chitosan nanoparticle suspension appears to be promising enough for effective management of ocular viral infections.